2017
DOI: 10.1021/acs.inorgchem.7b01923
|View full text |Cite
|
Sign up to set email alerts
|

H-Bonding Assisted Self-Assembly of Anionic and Neutral Ligand on Metal: A Comprehensive Strategy To Mimic Ditopic Ligands in Olefin Polymerization

Abstract: Self-assembly of two neutral ligands on a metal to mimic bidentate ligand coordination has been frequently encountered in the recent past, but self-assembly of an anionic ligand on a metal template alongside a neutral ligand remains an elusive target. Such a self-assembly is hampered by additional complexity, wherein a highly negatively charged anion can form intermolecular hydrogen bonding with the supramolecular motif, leaving no scope for self-assembly with neutral ligand. Presented here is the self-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…After the imidazolium-based cations, which contain only H-bond donor unit(s), we considered 1,4-diazabicyclo[2.2.2]­octane (DABCO), which should result in the 1,4-diazabicyclo[2.2.2]­octan-1-ium cation VII with both H-bond acceptor and H-bond donor sites and thus capable of functioning in a ditopic manner. Compound 14 was obtained by treating the ligand 1 with 1 equiv of DABCO and crystallized from a hot DMF/CH 3 OH mixture (Scheme ). So far, we were unable to obtain high-quality single-crystal X-ray diffraction data, and therefore, we are not discussing any metric parameters of this compound (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…After the imidazolium-based cations, which contain only H-bond donor unit(s), we considered 1,4-diazabicyclo[2.2.2]­octane (DABCO), which should result in the 1,4-diazabicyclo[2.2.2]­octan-1-ium cation VII with both H-bond acceptor and H-bond donor sites and thus capable of functioning in a ditopic manner. Compound 14 was obtained by treating the ligand 1 with 1 equiv of DABCO and crystallized from a hot DMF/CH 3 OH mixture (Scheme ). So far, we were unable to obtain high-quality single-crystal X-ray diffraction data, and therefore, we are not discussing any metric parameters of this compound (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Balaraman group (IISER-Tirupati) efforts lie in the domain of catalytic hydrogenation and dehydrogenation reactions (Midya et al, 2015;Sahoo et al, 2017;Sahoo et al, 2018;Jaiswal et al, 2017;Nandakumar et al, 2015). Chikkali group (CSIR-NCL) uses metal catalysts bearing phosphorus ligands featuring supramolecular binding property for hydrophosphination, hydrogenation, hydroformylation, polymerization reactions (Koshti et al, 2014;Koshti et al, 2015;Pandey and Chikkali, 2015;Pandey et al, 2018;Mote et al, 2017). Biplab group (IISERK) is developing new synthetic methodology using manganese catalyst to construct new C-C bonds by alcohols activation (Barman et al, 2018a;Maji and Barman, 2017;Barman et al, 2018b;Jana et al, 2018).…”
Section: Organometallic Catalysismentioning
confidence: 99%
“…Whereas, the corresponding Pd-complexes produced ethylene oligomers (Figure 1C, 2). It has been recently demonstrated that an aminocarboxylate ligated nickel complex can catalyze ethylene dimerizationr eaction in presence of suitablea ctivator.I nt he view of prior art in this field [12,13] and our previous work, [14][15][16] we envisioned that an iminocarboxy ligated metal complex might catalyze the ethylene polymerization reaction. [10] While, specially designed ligand backbone comprising N-heterocyclic carbene were found to be active in ethylene polymerization (Figure 1C, 4).…”
Section: Introductionmentioning
confidence: 97%
“…[11] Based on the above discoveries, we pondered about the choice of the bidentate ligand that can yield single component neutralm etal complex, which may catalyzee thylene polymerization reaction. It has been recently demonstrated that an aminocarboxylate ligated nickel complex can catalyze ethylene dimerizationr eaction in presence of suitablea ctivator.I nt he view of prior art in this field [12,13] and our previous work, [14][15][16] we envisioned that an iminocarboxy ligated metal complex might catalyze the ethylene polymerization reaction.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation